2009
DOI: 10.3109/02813430903226530
|View full text |Cite
|
Sign up to set email alerts
|

Effect of educational outreach on general practice prescribing of antibiotics and antidepressants: A two-year randomised controlled trial

Abstract: A simple, group-level educational outreach intervention, designed to take account of identified barriers to change, can have a modest but sustained effect on prescribing levels. However, outreach is not always effective. The context in which change in prescribing practice is being sought, the views of prescribers concerning the value of the drug, or other unrecognised barriers to change may influence the effectiveness of outreach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 14 publications
1
31
0
1
Order By: Relevance
“…In primary care (table 2 ), 33 studies (70%) [ 20 24 , 26 , 27 , 29 , 30 , 32 39 , 41 , 44 , 45 , 47 , 48 , 50 , 51 , 53 , 54 , 56 , 58 61 , 63 , 65 ] focused on the use of antibiotics in respiratory infections, and one focused on the use of antibiotics in infectious diseases and other infections (urinary infections, skin and soft tissue infections and septicemia) [ 27 ]; the remaining 30% failed to identify any target disease [ 25 , 28 , 31 , 40 , 42 , 43 , 46 , 49 , 52 , 55 , 57 , 62 , 64 , 66 ]. Of the 47 papers, 27 (57%) studied the efficacy/effectiveness of one or more interventions versus non-intervention, using a control group that received the intervention in four studies, dissemination of guideline information in three [ 56 , 57 , 65 ] and educational sessions on diagnosis of otitis media in one [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In primary care (table 2 ), 33 studies (70%) [ 20 24 , 26 , 27 , 29 , 30 , 32 39 , 41 , 44 , 45 , 47 , 48 , 50 , 51 , 53 , 54 , 56 , 58 61 , 63 , 65 ] focused on the use of antibiotics in respiratory infections, and one focused on the use of antibiotics in infectious diseases and other infections (urinary infections, skin and soft tissue infections and septicemia) [ 27 ]; the remaining 30% failed to identify any target disease [ 25 , 28 , 31 , 40 , 42 , 43 , 46 , 49 , 52 , 55 , 57 , 62 , 64 , 66 ]. Of the 47 papers, 27 (57%) studied the efficacy/effectiveness of one or more interventions versus non-intervention, using a control group that received the intervention in four studies, dissemination of guideline information in three [ 56 , 57 , 65 ] and educational sessions on diagnosis of otitis media in one [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-nine studies (62%) [ 20 23 , 25 – 27 , 29 , 34 , 36 39 , 41 , 44 , 45 , 47 – 50 , 52 , 53 , 55 , 60 65 ] reported positive results for all outcomes measured; fourteen studies (30%) [ 24 , 31 , 32 , 35 , 40 , 42 , 43 , 46 , 51 , 54 , 57 59 , 66 ] reported positive results for some outcomes, and results that were not statistically influenced by the intervention for others; only four studies [ 28 , 30 , 33 , 56 ] failed to report significant post-intervention improvements for all outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prescribing has been described as done in a habitual manner [3,23–25], based on the trust of broad-spectrum antibiotics as being more effective [26], and being influenced by the structure of the healthcare system [25]. In primary care the patient–physician relationship seems to influence how antibiotics are prescribed [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…There are several different studies assessing the efficacy of measures that can be taken to reduce prescribing of antibiotics for UAI. Education of both parents and health professionals, educational videos playing in emergency service waiting rooms and information leaflets can all be effective (1,(25)(26)(27) .…”
Section: Discussionmentioning
confidence: 99%